Rationale for withholding professional resuscitation in emergency medical system-attended out-of-hospital cardiac arrest. (January 2022) - Yap, Justin; Haines, Morgan; Nowroozpoor, Armin; Armour, Richard; Luongo, Allessandra; Sidhu, Gurwinder; Scheuermeyer, Frank; Hutton, Jacob; Helmer, Jennie; Bolster, Jennifer; Puyat, Joseph; Christenson, Jim; et al.
Abstract: Background: Half of out-of-hospital cardiac arrests (OHCA) are deemed inappropriate for resuscitation by emergency medical services (EMS). We investigated patient characteristics and reasons for non-treatment of OHCAs, and determined the proportion involving illicit drug use. Methods: We reviewed consecutive EMS-untreated OHCA from the British Columbia Cardiac Arrest Registry (2019–2020). We abstracted patient characteristics and categorized reasons for EMS non-treatment: (1) prolonged interval from the OHCA to EMS arrival ("non-recent OHCA") with or without signs of "obvious death"; (2) do-not-resuscitate (DNR) order; (3) terminal disease; (4) verbal directive; and (5) unspecified. We abstracted clinical details regarding a history of, or evidence at the scene of, illicit drug use. Results: Of 13 331 cases, 5959 (45%) were not treated by EMS. The median age was 67 (IQR 54–81) and 1903 (32%) were female. EMS withheld resuscitation due to: non-recent OHCA, with and without signs of "obvious death" in 4749 (80%) and 108 (1.8%), respectively; DNR order in 952 (16%); terminal disease in 77 (1.3%); family directive in 41 (0.69%); and unspecified in 32 (0.54%). Overall and among those with non-recent OHCA, 695/5959 (12%) and 691/4857 (14%) had either a history of or evidence of recent illicit drug use, respectively. Conclusion: A prolonged interval from the OHCA until EMS assessment was the predominant reason for withholding treatment. Innovative solutions to decrease this interval may increase the proportion of OHCA that are treated by EMS and overall outcomes. Targeted interventions for illicit-drug use-related OHCAs may add additional benefit.